PICTURE OF FASTING BLOOD GLUCOSE LEVELS IN HYPERTENSION PATIENTS AT TOTO KABILA REGIONAL GENERAL - Nirmawati Masalam; Erfan AR Lainjong; Marlia (LPPM Universitas Bina Mandiri Gorontalo, 2026)
Hypertension is a chronic condition that significantly increases the risk of cardiovascular and metabolic complications. Impaired blood glucose regulation is a common complication, making fasting blood glucose (FBG) monitoring essential for early detection of metabolic disorders, particularly diabetes mellitus. Objective: This study aims to describe the profile of FBG levels among hypertensive patients at Toto Kabila Regional General Hospital. Methods: A quantitative descriptive study with a cross-sectional approach was conducted between July and August 2025. A sample of 27 hypertensive patients was selected using a purposive sampling technique. FBG levels were measured using the Point of Care Testing (POCT) method. Results: The findings revealed that out of 27 patients, 10 individuals (37%) had normal FBG levels (70–126 mg/dL), while 17 individuals (63%) exhibited abnormal levels (<70 or >126 mg/dL). The mean FBG value was 228.52 mg/dL, indicating a high prevalence of hyperglycemia in the study population. Conclusion: The majority of hypertensive patients at Toto Kabila Regional General Hospital have abnormal fasting blood glucose levels. These results provide critical baseline data for healthcare providers to implement early prevention and management strategies for metabolic complications in hypertensive patients.